Sustainable culture in the purchase of organic cosmetics - Vargas Zhumilima, Keyla; Góngora Vite, Paola; Bonisoli, Lorenzo (mktDESCUBRE; Vol 1 No 22 (2023): Twenty-second Edition (July - December)DO - 10.36779/mktdescubre.v1i22.836, 2023)
Green culture is transforming the cosmetics industry towards more. The fundamental purpose of this research lies in the scrutiny of the interconnected relationships between green culture, pro-environmental behavior and purchase intention of green cosmetic products. To achieve this goal, a solid quantitative analysis methodology has been used. A critical component of our research was the application of the SEM/PLS analysis tool, which allowed for detailed and accurate analysis of the collected data. The results obtained provide clarity about the complex relationship between fundamental factors in purchasing decision making. A central finding of this study reveals that ecological culture has a direct and substantial impact on the purchase intention of ecological cosmetic products. On the other hand, it was found that ecological culture does not exert a significant indirect effect on the purchase intention of ecological cosmetics when pro-environmental behavior is considered as a moderator. Among the most important conclusions, environmental culture is highlighted as a substantial variable when purchasing organic cosmetics.